Effect of incremental exercise on initiation and movement times in a choice response, whole body psychomotor task. Issue 8 (25th July 2005) - McMorris, T; Delves, S; Sproule, J; Lauder, M; Hale, B
Abstract : Objectives: To examine how exercise at moderate and maximal intensities affects performance on a choice response time, whole body psychomotor task. Methods: Subjects (n  =  12) were tested on a three-choice response time task, after rest and after exercise at 70% and 100% maximum power output (W˙max ). The dependent variables were time to begin forward momentum (initiation time) and time to complete the movement (movement time). Stride time for the first and second strides and number of strides to cover first 1.1 m were also measured. Blood lactate concentrations and heart rate were recorded before and after completion of each psychomotor test. The subjects subjectively assessed the amount of effort that they used to complete the task. Results: Repeated measures analysis of variance showed a significant effect for initiation ( F 2, 22  =  11.47, p<0.001) and movement times ( F 2, 22  = 14.61, p<0.001). Post hoc least significant difference (LSD) tests showed that initiation time after exercise at 70% W˙max was significantly faster than that in the other two conditions. Speed of initiation after rest was significantly quicker than that after exercise at W˙max . For movement time, LSD tests showed that time after maximal exercise was significantly slower than that in the other two conditions. Stride time for the second stride showed a significant effect ( F 2, 22  =  6.20, p<0.01). LSD tests found that time after exercise at W˙max was significantly slower in the other two conditions. Stepwise multiple regression analyses found that the increment of change, from rest, of lactate concentrations could significantly predict the increment of change in initiation ( R 2  =  0.40) and movement ( R 2  =  0.50) times. Conclusions: Exercise affects a whole body task differently from purely cognitive tasks. Central factors are probably more important than peripheral factors.